Peran Interaksi Sosial dalam Pembentukan Karakter Anak Prasekolah di Desa Sembalun - M Saipul Watoni; Muh. Jaelani Al-Pansori; Muh. Taufiq; Lia Rismawati (Lembaga Bale Literasi, 2024)
This study aims to examine the role of social interaction in the character development of preschool children in Sembalun Village, Lombok. The main focus of this research is to identify the impact of interactions with family, early childhood education (PAUD) institutions, and peers on children's character development. A qualitative approach with a case study method was used, involving direct observation, interviews, and documentation. The findings reveal that the family plays a fundamental role in instilling core character values such as honesty, responsibility, and discipline. Additionally, PAUD institutions in Sembalun support character development through culturally-based approaches and group activities that promote empathy, tolerance, and cooperation. Interaction with peers also significantly contributes to social learning, where children learn to manage conflicts, share, and appreciate differences. This study emphasizes the importance of collaboration between families, educational institutions, and communities in supporting the early character development of children. The findings are expected to contribute to the development of early childhood education policies, particularly in rural areas with strong local cultural traditions.